(untitled) (مجلة الفاروق للعلوم, 2026)
A Landsat-5 TM digital spectral data covers Weixi area which lies in the North West of Yunnan Province, China, which is commonly called as ‘three river’ . Different image processing algorithms have been evaluated in the context of geological mapping using Landdsat TM data. False color composites, the principal component imagery, and IHS decorrelation stretching method for Landsat-5 TM data have been found useful in delineating the regional geological features, mainly to provide the maximum geological information for area of study. The study testifies that using different image processing yields best results for geological mapping in arid and semiarid regions by preserving morphological and spectral information. Generally, the study area can be divided into three main geological units: Basaltic intrusive rocks, Metamorphic with varying intensities and Sedimentary rocks.